2023
DOI: 10.1002/cam4.5681
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular features related to exceptional therapy response and extreme long‐term survival in glioblastoma

Abstract: Glioblastoma Multiforme (GBM) remains the most common malignant primary brain tumor with a dismal prognosis that rarely exceeds beyond 2 years despite extensive therapy, which consists of maximal safe surgical resection, radiotherapy, and/or chemotherapy. Recently, it has become clear that GBM is not one homogeneous entity and that both intra-and intertumoral heterogeneity contributes significantly to differences in tumoral behavior which may consequently be responsible for differences in survival. Strikingly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 159 publications
(387 reference statements)
0
8
0
Order By: Relevance
“…With a survival of 71 months (and still counting) this is 4.7 times longer than the median survival of a GBM patient receiving SoC treatment (i.e. 15 months) (Grochans et al, 2022), and this patient can be considered a "long-term survivor" (Decraene et al, 2023). This suggests that this patient is not only an outlier at the molecular level, as our models have demonstrated, but also in a clinical context.…”
Section: Macrophage/gam -Gscc Interactions Correlate With Clinical Ou...mentioning
confidence: 61%
See 1 more Smart Citation
“…With a survival of 71 months (and still counting) this is 4.7 times longer than the median survival of a GBM patient receiving SoC treatment (i.e. 15 months) (Grochans et al, 2022), and this patient can be considered a "long-term survivor" (Decraene et al, 2023). This suggests that this patient is not only an outlier at the molecular level, as our models have demonstrated, but also in a clinical context.…”
Section: Macrophage/gam -Gscc Interactions Correlate With Clinical Ou...mentioning
confidence: 61%
“…Given the substantial heterogeneity and the consistent failure of current therapies in GBM, it is important to explore and develop more individualized GBM treatment strategies. Even though most clinical studies for GBM treatment have failed, there are often exceptional responders who benefit from a particular therapy (Decraene et al, 2023). The development and clinical validation of new preclinical models based on patient-derived samples that allow for a more precise reproduction of the patient's tumor complexity will facilitate a more accurate assessment of whether patients will respond to a specific treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The implications of the tumor microenvironment on glioblastoma progression also extend to immune cell interactions, which have been established to play a significant role on phenotype and prognosis. Tumor associated macrophages, specifically monocytes, make up the largest non‐neoplastic cell population in the glioblastoma tumor microenvironment, making their activity a natural point of interest 45 . They are known to promote tumor growth by suppressing effector T‐cell function, and stimulating tumor proliferation through secretion of pro‐angiogenic and pro‐mitogenic factors, such as transforming growth factor‐beta (TGF‐β) 45,46 .…”
Section: The Multilayered Organization Of Glioblastoma Heterogeneitymentioning
confidence: 99%
“…Tumor associated macrophages, specifically monocytes, make up the largest non‐neoplastic cell population in the glioblastoma tumor microenvironment, making their activity a natural point of interest 45 . They are known to promote tumor growth by suppressing effector T‐cell function, and stimulating tumor proliferation through secretion of pro‐angiogenic and pro‐mitogenic factors, such as transforming growth factor‐beta (TGF‐β) 45,46 . Interestingly, a recent study found that macrophages have a causal role in inducing the MES‐like state transition in glioblastoma cells 47 .…”
Section: The Multilayered Organization Of Glioblastoma Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation